2019
DOI: 10.3390/jmse7100374
|View full text |Cite
|
Sign up to set email alerts
|

Grid Type and Turbulence Model Influence on Propeller Characteristics Prediction

Abstract: This paper evaluates the applicability of the hexahedral block structured grids for marine propeller performance predictions. Hydrodynamic characteristics for Potsdam Propeller Test Case (PPTC), namely thrust and torque coefficients, were determined using numerical simulations in two commercial solvers: Ansys Fluent and STAR-CCM+. Results were attained for hexahedral and tetrahedral hybrid grids equivalent in terms of cell count and quality, and compared to the experimental results. Furthermore, accuracy of Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…The highest level of errors for the open water efficiency coefficients reaches a value slightly larger than 5% for the highest advance ratio, at which the thrust and torque have the lowest values over the domain, as Figure 4 bears out. The numerical solutions reported here are very similar to those reported in [38], even though the solvers were different and the closure to turbulence was achieved by using different models. Moreover, the present solutions are in a good agreement with most of those reported in [39], where various solvers were used to solve the benchmark case of the PPTC propeller by 14 attendees of the symposium.…”
Section: Grid Convergence Testsupporting
confidence: 67%
“…The highest level of errors for the open water efficiency coefficients reaches a value slightly larger than 5% for the highest advance ratio, at which the thrust and torque have the lowest values over the domain, as Figure 4 bears out. The numerical solutions reported here are very similar to those reported in [38], even though the solvers were different and the closure to turbulence was achieved by using different models. Moreover, the present solutions are in a good agreement with most of those reported in [39], where various solvers were used to solve the benchmark case of the PPTC propeller by 14 attendees of the symposium.…”
Section: Grid Convergence Testsupporting
confidence: 67%
“…Therefore, it was selected as the preferred approach for this study. Previous researches have shown that k- model and sliding mesh deliver sufficient accurate results [2,4,6]. Therefore, the k-epsilon turbulence model is conducted for each simulation case.…”
Section: The Numerical Methodology and Physical Modelmentioning
confidence: 99%
“…The numerical approach utilized for solving the Reynolds-averaged Navier-Stokes (RANS) equation is currently extensively utilized, yielding enhanced accuracy in the determination of solutions and flow characteristics [1]. Sikirica et al [2] investigated the effects of grid type and turbulence model on the prediction of propeller characteristics. Similar findings were obtained by the Realizable k- and SST k- models, however the Realizable model proved to be more precise and consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Sikiraka et al analyzed marine propeller using structured grid and unstructured grid. Analysis is performed for open water characteristics and cavitating flow on Potsdam VP1304 [33]. For cavitating flows, the error is less than 2% compared to experimental results.…”
Section: Literature Reviewmentioning
confidence: 99%